The influence of foreign languages on L1: the case of intervocalic stop occlusion - Sypiańska, Jolanta (Neofilolog, 2021)
The aim of the article is to investigate cross-linguistic influence (CLI) of foreign languages on the L1 also referred to as L1 drift. The influence is measured by means of the degree of intervocalic stop occlusion in all the languages of L1 Polish, L2 Spanish and L3 English multilinguals. Although Polish is a language with no systemic spirantization of intervocalic stops, the assumption is that if L1 Polish is under the influence of L2 Spanish in multilinguals the degree of intervocalic stop occlusion may be lower in the otherwise non-spirantized context in L1 Polish. The degree of intervocalic stop occlusion is calculated with measures of intensity: Cmin, Vmax; but also with measures of relative intensity used in spirantization research: IntDiff and IntRatio. The results show that only Cmin and Vmax effectively capture the influence of L2 on L1, whereas the extent of the influence is conditioned by how well the speakers master spirantization in their L2 Spanish. Finally, as predicted, the L3 does not constitute a source of influence for the L1.